1986
DOI: 10.1007/bf01870703
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic mechanism of Na+, K+, Cl−-cotransport as studied by Rb+ influx into HeLa cells: Effects of extracellular monovalent ions

Abstract: Ouabain-insensitive, furosemide-sensitive Rb+ influx (JRb) into HeLa cells was examined as functions of the extracellular Rb+, Na+ and Cl- concentrations. Rate equations and kinetic parameters, including the apparent maximum JRb, the apparent values of Km for the three ions and the apparent Ki for K+, were derived. Results suggested that one unit molecule of this transport system has one Na+, one K+ and two Cl- sites with different affinities, one of the Cl- sites related with binding of Na+, and the other wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…However, using a simple competition experiment, we verified that the two cations have similar binding affinities for the cotransporter. These results are supported by studies that showed similar binding constants for K ϩ and Rb ϩ in HeLa cells (35,36), Madin-Darby canine kidney (MDCK) cells (1), and Ehrlich ascites tumor cells (21 (17)] movement likely represents a combination of Na-K-2Cl cotransport (shaded columns in Fig. 5) and other NKCC1-mediated modes of transport.…”
Section: Discussionsupporting
confidence: 62%
“…However, using a simple competition experiment, we verified that the two cations have similar binding affinities for the cotransporter. These results are supported by studies that showed similar binding constants for K ϩ and Rb ϩ in HeLa cells (35,36), Madin-Darby canine kidney (MDCK) cells (1), and Ehrlich ascites tumor cells (21 (17)] movement likely represents a combination of Na-K-2Cl cotransport (shaded columns in Fig. 5) and other NKCC1-mediated modes of transport.…”
Section: Discussionsupporting
confidence: 62%
“…Affinity of the Na + /K + /2Cl -cotransporter for the K + surrogate Rb + increases in HeLa cells when bathing saline Na + concentration increases (Miyamoto et al, 1986). Doublereciprocal plots of Rb + uptake vs Rb + concentration in the bath show that increases in Na + concentration in the bath reduce Kt for K + transport without affecting Jmax (Miyamoto et al, 1986).…”
Section: Na + Competes With K + For Transportmentioning
confidence: 98%
“…The most common finding is that increasing bathing saline Na + concentration produces an increase in K + flux through bumetanide-sensitive Na + /K + /2Cl -cotransporters (for reviews, see Russell, 2000;Haas and Forbush, 2000;Mount et al, 1998). Transport of K + by the Na + /K + /2Cl -cotransporter is stimulated by increases in bathing saline Na + concentration in HeLa cells (Miyamoto et al, 1986), duck erythrocytes (Haas and McManus, 1982) and renal epithelial cell lines (Rindler et al, 1982;Brown and Murer, 1985). Affinity of the Na + /K + /2Cl -cotransporter for the K + surrogate Rb + increases in HeLa cells when bathing saline Na + concentration increases (Miyamoto et al, 1986).…”
Section: Na + Competes With K + For Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in the cellular Cl-concentration after treatment with NaNO3 or NaNO2 may be caused by replacement of cellular Cl with the permeant anion, NO3-or NO2-, by accelerated Cl-extrusion as the Na+ concentration increases, or both. A considerable part of Na+ or K+ transport has been linked to Cl-transport in cultured cells (10,11,13); but, lack of change in the cellular K+ concentration suggests that K+ pumping activity (i.e. Na, K-ATPase activity) functions normally during exposure to Na salts.…”
Section: Discussionmentioning
confidence: 99%